P2.101 HIV Status and Other Predictors of Successful Syphilis Treatment. (13th July 2013) - Kohn, R P; Bernstein, K; Cohen, S; Chen, M; Philip, S
Abstract : Background: Data addressing the question of whether HIV-positive patients respond as well to the recommended treatment for syphilis as HIV-negative patients are sparse. We examined data from reported early syphilis cases in San Francisco to identify factors related to serologic response to treatment. Methods: San Francisco early syphilis cases diagnosed between 2006 and 2012 were analysed in terms of serologic response to treatment. Cases were excluded if the patient had any prior syphilis diagnosis reported, and only cases with an initial reactive serologic test for syphilis (STS) titer of 1:4 or higher were included. A successful serologic response to treatment was defined by a record of a non-reactive STS or a four-fold titer decrease within 12 months from treatment. Survival analysis and proportional hazards models were used to examine the relationship between demographic and risk factor data, including HIV status, and number of days until successful serologic response was documented. Results: A total of 1664 first-time cases were examined. HIV-positive patients were significantly more likely to have a follow-up STS than other patients (p < 0.0001). Of the 1557 cases with any follow-up STS, 9.3 percent did not show evidence of successful serologic response. HIV-negative patients were not found to be less likely to show response to treatment (median of 111 days for HIV-positives versus 124.5 for HIV-negatives, p < 0.0001). Stage of disease was also associated with evidence of serologic response (median of 121.0 days for primary, 109.0 days for secondary, and 130.0 for early latent), but race, gender, genders of partners, and treatment provided were not. Conclusion: Analysis of routine interview data found no evidence that HIV-positive patients failed to respond to standard syphilis treatments. However, the limits of surveillance data suggest the need for further research examining the relationship between immune status and response to treatment among HIV-positive patients.